Quantum-mechanical approaches in evaluating the contact interaction of tribosystems - Zaspa, Yu.; Dykha, A. (Problems of Tribology, 2020)
The physical mechanisms of the formation and transformation of corpuscular-vortex-wave thermal complexes in contact tribosystems based on the quantum-mechanical exchange interaction in ensembles of identical quasiparticles are considered. The presence of contact discontinuity of two thermostats with different signs of absolute temperature determines the generation of pairs of quasiparticle perturbations stabilized along the wavelength in cooperation with photons of stimulated thermal radiation, and also in frequency in interaction with phonons. Internal instability and collapse processes in such a system of perturbations lead to the formation of defects in the material of the tribocouple and are the cause of emergency friction conditions. Specific technical examples of thermal complex generation during fretting, sliding and rolling friction, and cutting are given. A corpuscular-vortex-wave mechanism of selective transfer and hydrogen wear in tribosystems is proposed